Near-Infrared Light Exposure Triggers ROS to Downregulate Inflammatory Cytokines Induced by SARS-CoV-2 Spike Protein in Human Cell Culture - Blanche Aguida; Marie-Marthe Chabi; Soria Baouz; Rhys Mould; Jimmy D. Bell; Marootpong Pooam; Sebastien André; Dominique Archambault; Margaret Ahmad; Nathalie Jourdan (MDPI AG, 2023)
The leading cause of mortality from SARS-CoV-2 is an exaggerated host immune response, triggering cytokine storms, multiple organ failure and death. Current drug- and vaccine-based therapies are of limited efficacy against novel viral variants. Infrared therapy is a non-invasive and safe method that has proven effective against inflammatory conditions for over 100 years. However, its mechanism of action is poorly understood and has not received widespread acceptance. We herein investigate whether near-infrared (NIR) light exposure in human primary alveolar and macrophage cells could downregulate inflammatory cytokines triggered by the SARS-CoV-2 spike (S) protein or lipopolysaccharide (LPS), and via what underlying mechanism. Our results showed a dramatic reduction in pro-inflammatory cytokines within days of NIR light treatment, while anti-inflammatory cytokines were upregulated. Mechanistically, NIR light stimulated mitochondrial metabolism, induced transient bursts in reactive oxygen species (ROS) and activated antioxidant gene transcription. These, in turn, downregulated ROS and inflammatory cytokines. A causal relationship was shown between the induction of cellular ROS by NIR light exposure and the downregulation of inflammatory cytokines triggered by SARS-CoV-2 S. If confirmed by clinical trials, this method would provide an immediate defense against novel SARS-CoV-2 variants and other inflammatory infectious diseases.